Journalism Research in Germany: Origins, theoretical innovations and future outlook - Hanitzsch, Thomas (Brazilian journalism research, 2006)
In Germany, the study of journalism has a long tradition. Löﬀ elholz (2004b) identiﬁ ed the work of the writer and literary historian Robert Eduard Prutz (1816-1872) as being the ancestor of journalism theory. In 1845, long before the establishment of newspaper studies (“Zeitungskunde”) as a ﬁ eld of research, Prutz published “The History of German Journalism.” In later years the theoretical study of journalism was dominated by normative approaches, which continued for many decades. The belief that journalistic talent, similar to artistic talent, lies in the personality of the journalist (see Dovifat 1962) endured well into the 1970’s. At this time the scholarly discussion was mainly centered on the journalist as an individual who could barley live up to the normative expectations placed on news people. The result was a long-lasting (into the 1990s) array of often romantic demands on journalists which they could hardly fulﬁ ll.